2022
DOI: 10.1158/0008-5472.can-22-0848
|View full text |Cite
|
Sign up to set email alerts
|

Loss of LOXL2 Promotes Uterine Hypertrophy and Tumor Progression by Enhancing H3K36ac-Dependent Gene Expression

Abstract: Lysyl oxidase-like 2 (LOXL2) is a member of the scavenger-receptor cysteine-rich (SRCR) repeat carrying LOX family. Although LOXL2 is suspected to be involved in histone association and chromatin modification, the role of LOXL2 in epigenetic regulation during tumorigenesis and cancer progression remains unclear. Here, we report that nuclear LOXL2 associates with histone H3 and catalyzes H3K36ac deacetylation and deacetylimination. Both the N-terminal SRCR repeats and the C-terminal catalytic domain of LOXL2 ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Lysyl oxidase-like 2 (LOXL2) is a member of the scavenger-receptor cysteine-rich (SRCR) family that carries LOX, which is related to histone binding and chromatin modification. Studies have demonstrated that LOXL2 is a tumor suppressor, and low expression of LOXL2 can promote the progress of uterine cancer and inhibit the efficacy of anti-PD-1 therapy [ 42 ]. Thus, CRGs may play an important role in the occurrence and development of several types of tumors, but with few studies in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Lysyl oxidase-like 2 (LOXL2) is a member of the scavenger-receptor cysteine-rich (SRCR) family that carries LOX, which is related to histone binding and chromatin modification. Studies have demonstrated that LOXL2 is a tumor suppressor, and low expression of LOXL2 can promote the progress of uterine cancer and inhibit the efficacy of anti-PD-1 therapy [ 42 ]. Thus, CRGs may play an important role in the occurrence and development of several types of tumors, but with few studies in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Lysyl oxidase-like 2 (LOXL2) is a member of the scavenger-receptor cysteine-rich (SRCR) family that carries LOX, which is related to histone binding and chromatin modi cation. Studies have demonstrated that LOXL2 is a tumor suppressor, and low expression of LOXL2 can promote the progress of uterine cancer and inhibit the e cacy of anti-PD-1 therapy 27 . Thus, CRGs may play an important role in the occurrence and development of several types of tumors, but with few studies in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the stained cells were analyzed via a flow cytometer (Beckman Coulter). [ 45 ] Data analysis was conducted using FlowJo software (BD, USA). The types of immune cells were subjected to density clustering after they were identified using nonlinear dimensionality reduction [t‐distributed stochastic neighbor embedding (t‐SNE)].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the sections were stained with 3,3′‐diaminobenzidine (DAB) for color development. [ 45 ] The slides were then counterstained with hematoxylin, dehydrated, and imaged under an optical microscope (Nikon, Japan).…”
Section: Methodsmentioning
confidence: 99%